Inorganic Polyphosphate in Escherichia coli: the Phosphate Regulon and the Stringent Response - Rao, Narayana N. (American Society for Microbiology, 1998)
Escherichia coli transiently accumulates large amounts of inorganic polyphosphate (polyP), up to 20 mM in phosphate residues (P(i)), in media deficient in both P(i) and amino acids. This transient accumulation is preceded by the appearance of nucleotides ppGpp and pppGpp, generated in response to nutritional stresses. Mutants which lack PhoB, the response regulator of the phosphate regulon, do not accumulate polyP even though they develop wild-type levels of (p)ppGpp when subjected to amino acid starvation. When complemented with a phoB-containing plasmid, phoB mutants regain the ability to accumulate polyP. PolyP accumulation requires high levels of (p)ppGpp independent of whether they are generated by RelA (active during the stringent response) or SpoT (expressed during P(i) starvation). Hence, accumulation of polyP requires a functional phoB gene and elevated levels of (p)ppGpp. A rapid assay of polyP depends on its adsorption to an anion-exchange disk on which it is hydrolyzed by a yeast exopolyphosphatase.